PENGARUH KEPEMIMPINAN DAN PELATIHAN DALAM MENINGKATKAN KINERJA KARYAWAN PADA HOTEL THE PATRA BALI RESORT & VILLAS - Ayu Ega Oktaviany; I Nengah Aristana (Universitas Triatma Mulya, 2020)
Human resources are the main role of a company because it can create various innovations to move the company. In order for the company to be more advanced, it must have leadership knowledge and skills that are appropriate to the field and business in managing the company. Improving employee performance is a priority made by each company to run in accordance with the company's vision and mission. One way to improve the performance of human resources is by providing training programs. The Patra Bali Resort & Villas has several aspects of assessment in improving employee performance, namely, quality of work, knowledge of work, quantity of work, level of attendance, responsibility, expertise, honesty. This research was conducted at The Patra Bali Resort & Villas with a total employee of 238 people consisting of 11 departments. The sample taken in this study amounted to 100 people calculated using Solvin formula withtechnique Proportional Sampling. The data analysis tool used is descriptive analysis, data quality test, classic assumption test and multiple linear regression test with the application Statistical Package For Social Science (SPSS) Version 24.0. The results showed that leadership and training had a positive effect on employee performance with a determination coefficient of 0.217 or 21.7% while the remaining 78.3% was influenced by other factors outside of this study. Hypothesis test results of leadership influence (X1) on employee performance (Y) show a significance level of 0.029 smaller than α = 0.05. This means that leadership influences employee performance. Leadership regression coefficient (X1) of 0.182 indicates a positive influence of leadership on employee performance. These results accept the hypothesis H1 which states leadership has a positive effect on employee performance and the results of the training hypothesis test (X2) on employee performance (Y) in Table 4.5 shows a significance level of 0.003 smaller than α = 0.05. This means that the training variable has an effect on employee performance. The regression coefficient of the training variable (X2) of 0.373 indicates a positive effect of training on employee performance. This result accepts the hypothesis H2 which states that training has a positive effect on employee performance The Patra Bali Resort & Villas